Future‐directed thinking in first‐episode psychosis. (29th October 2015) - Goodby, Emmeline; MacLeod, Andrew K.
Abstract : Objectives: This study employed the Future Thinking Task (MacLeod et al ., 2005, Br . J . Clin . Psychol., 44, 495) to investigate whether future‐directed thinking in first‐episode psychosis is significantly different from that of matched controls, and to identify its correlates in this patient group. Design: Cross‐sectional, mixed‐model, case–control design. Method: Participants were 30 patients with first‐episode psychosis and 27 matched controls. The Future Thinking Task was used to assess future‐directed thinking in both groups. Anxiety and depression were also measured as well as self‐report measures of hopelessness, suicide ideation and a measure of negative symptoms. Results: Individuals with psychosis were impaired in future‐directed thinking in both positive and negative domains, particularly with respect to the coming year. Increased self‐reported hopelessness was associated with reduced positive future thinking and increased negative future thinking. Increased positive future thinking was also associated with reduced severity of negative symptoms, whilst negative future thinking was associated with suicide ideation. Conclusions: Individuals with first‐episode psychosis show a reduction in positive future thinking in line with that seen in other clinical groups, but this is accompanied by an unexpected reduction in negative future thinking. The findings suggest a general disengagement with the future in this group that may affect recovery and functioning. Practitioner points: Individuals with first‐episode psychosis may benefit from interventions to help them engage with their future, in particular in the mid‐range, up to 1 year. The Future Thinking Task may be a helpful addition to the assessment of suicide risk in those with first‐episode psychosis. Decreased positive future thinking was associated with increased severity of negative symptoms, indicating a potential new treatment angle for this resistant aspect of psychosis. The cross‐sectional design of this study does not allow for conclusions about the causal relationship between psychosis and future‐directed thinking. This study investigated future‐directed thinking in individuals with a range of psychotic illnesses employing a trans‐diagnostic approach; therefore, conclusions cannot be drawn about the nature of future‐directed thinking in individual psychotic disorders.